DOES THE LAW OF ONE PRICE (LOP) HOLDS IN THE INTERNATIONAL BARLEY MARKETS - Sanusi Mohammed Sadiq; P I Singh; M M Ahmad (Agricultural Socio-Economics Journal, 2021)
A price time-series data of barley for a period of 49 years (1970-2019) sourced from the FAO database was used to determine the horizontal market integration of barley among some selected major market players in barley trade in the world. The chosen markets are Australia, Canada, Iran, Turkey and the USA based on the availability of up-to-date large span data. The collected data were analyzed using inferential statistics- unit root tests, co-integration tests, unrestricted vector autoregressive model, Granger causality test and impulse response function. The empirical evidence showed that the law of one price (LOP) exists among the selected markets i.e. there is perfect price communication among the markets in the long run, thus highly integrated. Besides, Australian and Canadian markets established a long-run equilibrium, thus have a stable price in the long run. Furthermore, the import and export hubs of barley in the trade are Canadian, USA and Turkey markets while Iranian and Australian markets are large consumer markets. The empirical evidence showed Canadian and USA markets to be the major players in the trade while the Australian market is a follower in the trade. All the selected markets have promising future prices with a little inflationary trend which will owe to supply fluctuation. The reinforcement of physical infrastructure, the use of ICTs and well-defined consistent agricultural policy/market initiatives would thus lead to the global creation of a single uniform economic market for barley.